Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18632/oncotarget.24625
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM shedding at the invasive front of the tumor is a marker of myometrial infiltration and promotes invasion in endometrioid endometrial cancer

Abstract: Endometrial cancer (EC) is the sixth deadliest cancer in women. The depth of myometrial invasion is one of the most important prognostic factors, being directly associated with tumor recurrence and mortality. In this study, ALCAM, a previously described marker of EC recurrence, was studied by immunohistochemistry at the superficial and the invasive tumor areas from 116 EC patients with different degree of myometrial invasion and related to a set of relevant epithelial and mesenchymal markers. ALCAM expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(62 reference statements)
2
8
0
Order By: Relevance
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…Studies have shown that the FGF19-FGFR4 signaling pathway was an effective antitumor target via mediating a lot of intracellular molecules [ 52 , 53 ]. CTNNB1 as an intermediate molecule between the FGF19-FGF4 signaling pathway and adhesion molecules such as ICAM1, CDH2 and ALCAM [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 58 ] was downregulated after EPS364 treatment. Hence, we speculated that EPS364 might target the FGF19-FGF4 signaling pathway to regulate the expression of adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem contradictory, but the difference between ALCAM function in vitro and in vivo indicates that ALCAM may be affected by the surrounding microenvironment. Notably, our results are consistent with those from previous reports regarding other carcinomas in which depletion of ALCAM suppresses cell proliferation and migration in vitro , but the cells demonstrate invasiveness in vivo [ 14 , 16 , 19 , 31 ]. For example, in cell lines of malignant mesothelioma and endometrioid endometrial cancer, proliferation and migration are inhibited in vitro by ALCAM silencing [ 16 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, in cell lines of malignant mesothelioma and endometrioid endometrial cancer, proliferation and migration are inhibited in vitro by ALCAM silencing [ 16 , 19 ]. Nevertheless, ALCAM-negativity at the invasive front of the tumor has been reported as a marker of myometrial invasion in tissue of endometrioid endometrial cancer [ 31 ]. Moreover, in a metastatic melanoma cell line, interfering with endogenous ALCAM through the expression of an amino-terminally truncated ALCAM, which disrupts ALCAM–ALCAM interactions, increases cell invasive growth in skin reconstructions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation